Project : collage. - Speight, Bev (London : Ilex Press, 2019)
Packed with great ideas for creating eye-catching collages, with 50 step-by-step projects to inspire you.
Collage -- Freehand -- Colour -- Build -- Spaces -- Texty -- Menagerie -- 3D -- Canvas -- Washi -- Surreal -- Distort -- Pattern -- Persona -- Joiners -- Mixology -- Repeat -- Fashion -- Inside out.
Published in association with the Tate Gallery.
Keywords: Collage